2019
DOI: 10.1002/pds.4894
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse birth outcomes after maternal varenicline use: A population‐based observational study in Denmark and Sweden

Abstract: Purpose: To examine risks of adverse birth outcomes in women exposed to varenicline during pregnancy.Methods: Population-based cohort study including live-born and stillborn infants from 1 May 2007 to 31 December 2012. Data from health and administrative registries in Denmark and Sweden, two Nordic countries with universal health care and routine registration of major life and health events. Infants were allocated to three cohorts on the basis of their in utero exposure: the exposed cohort consisting of infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Data will be pseudonymized before sent to the researcher. large studies, by using similar data from the Nordic countries (Denmark, Norway, Finland, Iceland, and Sweden) [30][31][32][33][34].…”
Section: Medical Research Using the Mbrmentioning
confidence: 99%
“…Data will be pseudonymized before sent to the researcher. large studies, by using similar data from the Nordic countries (Denmark, Norway, Finland, Iceland, and Sweden) [30][31][32][33][34].…”
Section: Medical Research Using the Mbrmentioning
confidence: 99%
“…There have been no randomised studies evaluating the effects of varenicline when used during pregnancy [83], and only one observational study of varenicline's effectiveness during pregnancy, finding that pregnant women using varenicline were almost threefold more likely to quit smoking than women using nicotine patches (RR 2.8, 95% CI 1.4 to 5.7) [85]. In the two controlled observational studies of the safety of varenicline during pregnancy that have been conducted, varenicline was not associated with an increased risk of adverse birth outcomes [86,87]. In the larger of these two studies, varenicline was found to reduce the risk of preterm birth and small for gestational age compared to women who smoked during pregnancy [87].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…When imported RWD are submitted for safety and/or efficacy evaluations, it may not be clear if regulatory agencies consider the transferability of RWD. For example, the FDA required the sponsor of varenicline (CHANTIX ® /CHAMPIX ® ) to submit a post-marketing safety study to compare pregnancy and birth outcomes among pregnant women exposed to varenicline with women who smoked during pregnancy and with non-smoking pregnant women ( 27 ). The sponsor submitted a population-based, prospective cohort study based on registries in Denmark and Sweden, countries that routinely track major life and health events, including pregnancy and birth outcomes ( 27 ).…”
Section: Key Observations From Selected Transferability Case Studiesmentioning
confidence: 99%
“…For example, the FDA required the sponsor of varenicline (CHANTIX ® /CHAMPIX ® ) to submit a post-marketing safety study to compare pregnancy and birth outcomes among pregnant women exposed to varenicline with women who smoked during pregnancy and with non-smoking pregnant women ( 27 ). The sponsor submitted a population-based, prospective cohort study based on registries in Denmark and Sweden, countries that routinely track major life and health events, including pregnancy and birth outcomes ( 27 ). The publicly available label update and supplemental approval letter note potential misclassification of the outcomes and exposure but do not comment on the use of data from outside the US ( 28 ).…”
Section: Key Observations From Selected Transferability Case Studiesmentioning
confidence: 99%